2019
DOI: 10.1029/2018wr024609
|View full text |Cite
|
Sign up to set email alerts
|

Fragmentation of the Hyporheic Zone Due to Regional Groundwater Circulation

Abstract: By use of numerical modeling and field observations, this work quantified the effects of catchment-scale upwelling groundwater on the hyporheic (below stream) fluxes over a wide range of spatial scales. A groundwater flow model was developed that specifically accounted for the hydrostatic and dynamic head fluctuations induced by the streambed topography. Although the magnitudes and relative importance of these streambed-induced fluxes were found to be highly sensitive to site-specific hydromorphological proper… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
45
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 21 publications
(52 citation statements)
references
References 80 publications
7
45
0
Order By: Relevance
“…HEFs (Figure 1) are driven by pressure gradients created by local streambed topographic variations and modulated by subsurface sediment architecture, combined with large-scale geomorphological and hydrogeological characteristics of the river network and adjacent aquifer systems, which can critically impact the spatial variability of HEF patterns [9,[39][40][41]. At the scale of the HZ, very small water level fluctuations drive changes in the hydraulic gradients across streambed bedform structures.…”
Section: Physical Drivers Of Hyporheic Exchange Flowsmentioning
confidence: 99%
See 3 more Smart Citations
“…HEFs (Figure 1) are driven by pressure gradients created by local streambed topographic variations and modulated by subsurface sediment architecture, combined with large-scale geomorphological and hydrogeological characteristics of the river network and adjacent aquifer systems, which can critically impact the spatial variability of HEF patterns [9,[39][40][41]. At the scale of the HZ, very small water level fluctuations drive changes in the hydraulic gradients across streambed bedform structures.…”
Section: Physical Drivers Of Hyporheic Exchange Flowsmentioning
confidence: 99%
“…The absolute gaining or losing of water from streams is a dynamic feature which can vary spatially and temporally. The fragmentation of coherent gaining or losing zones at the streambed interface strongly depends on the regional groundwater contribution [41]. In gaining streams, local regional groundwater systems discharge groundwater through the HZ into surface waters.…”
Section: Physical Drivers Of Hyporheic Exchange Flowsmentioning
confidence: 99%
See 2 more Smart Citations
“…In addition to the pressure distribution on the SWI, subsurface heterogeneity has a substantial impact on the subsurface flow field [12,13]. Heterogeneity in hydraulic conductivity influences the magnitude of subsurface flow velocity, as well as the size of the hyporheic zone [14,15]. Previous studies have shown that hydraulic conductivity decays with depth following an exponential function that can be estimated based on field measurements [16][17][18].…”
Section: Introductionmentioning
confidence: 99%